The application and mechanism of PD pathway blockade for cancer therapy. Issue 1107 (23rd September 2017) - Wang, Xing; Huang, Shan; Zhang, Ya; Zhu, Lin; Wu, Xiaoliang
Abstract: Research in cancer therapeutics has achieved major progress in the understanding of the tumour-immunity cycle, which controls the delicate balance between the immune system and tumour. Identification of cancer cell T-cell inhibitory signals, including PD-L1, has generated novel insight into how to reinvigorate the patients' immune cells to respond to a variety of tumour types. PD-1 and PD-L1 (PD) inhibitory pathway blockade appears to a highly promising therapy and could accomplish durable anti-tumour responses with a reasonable toxicity profile. Some of the FDA-approved mAbs can reverse the negative regulators from tumour cells and antigen presenting cells of T-cell function to treat some cancer types by blocking the PD signalling pathway, especially advanced solid tumours. Emerging clinical data suggest that cancer immunotherapy will become a significant part of the clinical treatment of cancer.